Founding Weimar violence and the German Revolution of 1918-1919 - Jones, Mark 1981- (Cambridge University Press, 2016)
The German Revolution of 1918–1919 was a transformative moment in modern European history. It was both the end of the German Empire and the First World War, as well as the birth of the Weimar Republic, the short-lived democracy that preceded the establishment of the Nazi dictatorship. A time of great political drama, the Revolution saw unprecedented levels of mass mobilisation and political violence, including the 'Spartacist Uprising' of January 1919, the murders of Karl Liebknecht and Rosa Luxemburg, and the violent suppression of strikes and the Munich Councils' Republic. Drawing upon the historiography of the French Revolution, Founding Weimar is the first study to place crowds and the politics of the streets at the heart of the Revolution's history. Carefully argued and meticulously researched, it will appeal to anyone with an interest in the relationship between violence, revolution, and state formation, as well as in the history of modern Germany
Keywords: Geschichte 1900-2000; Geschichte 1918-1919; Geschichte; Politik; Revolutions / Germany / History / 20th century; Political violence / Germany / History / 20th century; Political atrocities / Germany / History / 20th century; Münchener Räterepublik; Gewalt; Revolution; Weimarer Republik; Novemberrevolution; Vorgeschichte; Niederschlagung -- Politik; Politische Ordnung; Deutschland; Germany / History / Revolution, 1918; Germany / History / 1918-1933; Germany / Politics and government / 1918-1933